Intergranular corrosion of Cu-Al-Ni alloy in 0.5 mol dm−3 H2SO4 solution - Vrsalović, Ladislav (Array, 2020)
The corrosion behaviour of Cu-Al-Ni alloy in 0.5 mol dm–3 H2SO4 solution was investigated by electrochemical methods including open circuit potential measurement, electrochemical impedance spectroscopy measurements, linear and potentiodynamic polarization. Measurements were performed in 0.5 mol dm–3 H2SO4 at temperatures 20 and 40 °C. After polarization testing, corroded electrode surfaces were ultrasonically cleaned in deionized water and examined by light and scanning electron microscopy, while the elemental composition at individual points of the alloy surface was determined by EDS analysis. The results of the investigations revealed the occurrence of intergranular corrosion on the Cu-Al-Ni surface, which became more pronounced with increasing temperature.